Biomass solid electrolyte film and preparation method thereof, diaphragm-free solid-state battery, solid-state battery and mechanical device
By using biomass sugar to prepare lithiated solid electrolyte films, the problems of solid-state batteries in low ionic conductivity, short cycle life, and poor mechanical properties are solved, and efficient and safe solid-state batteries are improved.
Patent Information
- Application Number
- CN202411314498.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2044-09-20
AI Technical Summary
Existing solid-state batteries have problems in low ion conductivity, short cycle life, poor mechanical performance, poor processing performance and high cost, and traditional lithium-ion batteries lack high temperature performance and safety.
Lithified solid electrolyte films are prepared using biomass sugars. By mixing and polymerizing biomass sugars with alkaline lithium salts and polymer solid electrolyte monomers, a solid electrolyte film with excellent mechanical properties and high ionic conductivity is formed.
It improves the ionic conductivity and cycle life of solid-state batteries, enhances mechanical and safety performance, and reduces production costs, and realizes batch preparation of separator-free batteries.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solid-state batteries, and in particular to a biomass solid-state electrolyte film and a preparation method thereof, a diaphragm-free solid-state battery, a solid-state battery and a mechanical device. Background Art
[0002] Traditional lithium-ion batteries use liquid electrolytes and separators, which seriously affect the high temperature performance and safety of the battery, and the use of separators inevitably affects the energy density of the battery. In order to improve the energy density and safety of lithium-ion batteries, solid electrolyte membranes can be used to replace separators and liquid electrolytes. Biomass sugars are widely present in nature and have the advantages of low cost and wide sources. If biomass sugars can be fully utilized as raw materials for battery production, it will not only reduce the cost of battery production, but also provide new ideas for the development of solid-state batteries.
[0003] Solid-state batteries have many advantages. For example, solid electrolytes are non-flammable or non-combustible, which can effectively inhibit the growth of lithium dendrites, prevent short circuits, and improve the safety of solid-state batteries. However, there are still problems that need to be solved in completely replacing diaphragms and electrolytes with solid electrolytes, such as low ion conductivity, short cycle life, poor mechanical properties, poor processing performance, and high costs. Using biomass sugar in battery production can overcome the above problems of current solid-state batteries and is of great significance. Summary of the invention
[0004] The present invention aims to solve at least one of the technical problems in the related art to a certain extent. To this end, one object of the present invention is to provide a biomass solid electrolyte film and a preparation method thereof, a diaphragm-free solid-state battery, a solid-state battery and a mechanical device.
[0005] In a first aspect of the present invention, the present invention provides a method for preparing a biomass solid electrolyte film. According to an embodiment of the present invention, the method comprises: (1) mixing biomass sugar, alkaline lithium salt and a first solvent to obtain lithiated biomass sugar, wherein the biomass sugar comprises at least one of chitosan, alginic acid and cellulose; (2) mixing the lithiated biomass sugar, polymer solid electrolyte monomer, inorganic material, active lithium salt, initiator and second solvent and polymerizing them to obtain a precursor solution; (3) Applying the precursor solution on a substrate and drying it to obtain a biomass solid electrolyte film.
[0006] According to the method for preparing the biomass solid electrolyte film of the above embodiment of the present invention, first, biomass sugar, alkaline lithium salt and organic solvent are mixed to obtain lithiated biomass sugar, wherein the biomass sugar includes at least one of chitosan, alginate and cellulose. The biomass sugar material has a wide range of sources and can be obtained from nature. It is low-cost and can replace PVDF and PAA and other binders for use in positive and negative electrodes from the perspective of bonding. By lithiation-modified biomass sugar, lithium ions can be grafted onto the carboxyl or hydroxyl groups of biomass sugar to form a single ion conductor, which is beneficial to improve the lithium ion conductivity of the system. The electrolyte membrane will inevitably form a CEI film and a SEI film at the interface during the charge and discharge process, thereby consuming part of the active lithium ions, and the lithiated biomass sugar can make up for this part of the lost lithium ions, reduce the reduction in ionic conductivity caused by the loss of active lithium ions, and improve the stability of the positive and negative electrode interfaces and the first coulomb efficiency.
[0007] Lithiated biomass sugar can reduce the carboxyl and hydroxyl groups rich in the original biomass sugar. These groups are less stable than PVDF polymers in both the positive and negative electrodes. They will decompose under high pressure and corrode lithium metal under low pressure. Therefore, the content of the remaining carboxylic acid and hydroxyl groups can be controlled by regulating the degree of lithiation of biomass sugar. At this time, the content of unstable groups is much lower than that of biomass sugar in the unlithiated state, which improves the cycle performance of the battery. At the same time, carboxylic acid and hydroxyl groups can form cross-linked structures through hydrogen bonds, which improves the rigidity of the solid electrolyte membrane. Lithiated biomass sugar can improve the flexibility of the solid electrolyte membrane, thereby improving the overall mechanical properties of the solid electrolyte membrane. In summary, lithiated biomass sugar not only improves the mechanical properties of the solid electrolyte membrane and its ability to resist lithium dendrites, but also improves the battery cycle life.
[0008] Then, the lithiated biomass sugar, polymer solid electrolyte monomer, inorganic material, and active lithium salt are mixed and polymerized to obtain a precursor solution. The inventors also found that the lithiated biomass sugar can improve the compatibility of inorganic materials and polymer solid electrolyte monomers. The lithiated biomass sugar can form covalent bonds or hydrogen bonds with hydroxyl groups or oxides on the surface of inorganic materials, and the other end forms hydrogen bonds or generates covalent bonds with polymer solid electrolyte monomers, thereby organically connecting inorganic materials and polymer solid electrolyte monomers, which can not only wet the surface of inorganic materials, but also help to evenly disperse inorganic materials. Lithiated biomass sugar is a linear polymer. Through cross-linking polymerization with polymer solid electrolyte monomers and inorganic materials, the proportion of crystalline regions of the polymer can be greatly reduced, the mutual entanglement between chains can be reduced, the mobility of different polymer segments can be increased, and the sites for complexation and dissociation with lithium ions can be increased, thereby greatly enhancing the lithium ion transmission capacity. By combining the properties of rigid biomass sugar and flexible polymer monomers, a rigid-flexible approach is adopted to improve the continuity and flatness of the interface contact between the solid electrolyte and the positive and negative electrodes, and reduce the structural degradation caused by electrode volume changes.
[0009] Therefore, the solid electrolyte film prepared by this method has excellent mechanical strength and toughness, and strong processability. The solid-state battery prepared using the biomass solid electrolyte film has high ionic conductivity, can replace the diaphragm, prepare diaphragm-free batteries, and improve the battery cycle life and safety performance. This method is suitable for the production of diaphragm-free batteries, the raw material cost is controllable, and batch preparation of diaphragm-free batteries can be achieved.
[0010] In addition, the method for preparing a biomass solid electrolyte film according to the above embodiment of the present invention also has the following technical features: In some embodiments of the present invention, in step (1), the mass ratio of the alkaline lithium salt to the biomass sugar is (1-35):100.
[0011] In some embodiments of the present invention, the solid content of the system after the biomass sugar, the alkaline lithium salt and the first solvent are mixed is 10% to 25%.
[0012] In some embodiments of the present invention, in step (1), the mixing temperature is 20°C to 60°C.
[0013] In some embodiments of the present invention, the alkaline lithium salt includes at least one of lithium hydroxide, lithium carbonate and lithium hydride.
[0014] In some embodiments of the present invention, the first solvent includes at least one of N,N-dimethylacetamide, N-methylmorpholine-N-oxide, water, hydrochloric acid, formic acid, acetic acid and lactic acid.
[0015] In some embodiments of the present invention, in step (2), the mass ratio of the lithiated biomass sugar, the polymer solid electrolyte monomer, the inorganic material, and the active lithium salt is (15-25): (5-10): (50-90): (10-20).
[0016] In some embodiments of the present invention, in step (2), the polymerization includes photopolymerization or thermal polymerization.
[0017] In some embodiments of the present invention, the light source used for the photopolymerization includes ultraviolet light or visible light, and the time of the photopolymerization is 1 min to 60 min.
[0018] In some embodiments of the present invention, the heating temperature of the thermal polymerization is 30° C. to 120° C., and the heating time is 1 h to 80 h.
[0019] In some embodiments of the present invention, the polymer solid electrolyte monomer includes vinylidene fluoride, tetrafluoroethylene, ethylene oxide, vinylidene fluoride-hexafluoropropylene, hexafluoropropylene, 1,3,5-trioxane, 1,3-dioxane, 1,4-dioxane, 1,3-dioxolane, 1,4-dioxane, dithiolane, cycloborane, vinyl carbonate, vinyl sulfite, vinyl trithiocarbonate, vinyl acetate, methyl vinyl sulfone, ethyl vinyl sulfone, phthalic acid diacrylate, pentaerythritol tetraacrylate, methacrylate, At least one of ethylene glycol methacrylate, ethylene glycol dimethacrylate, ethylene glycol diacrylate, ethylene glycol acrylate, methyl methacrylate, propylene carbonate, acrylonitrile, lactam, lipoic acid, cyclopentane, alkyl disulfide, tetrakis(hydroxymethyl)phosphonium chloride, melamine, olefinated monophosphine ligand, bisphosphine ligand, arginine methyl ester, arginine ethyl ester, acrylamide, methoxypolyethylene glycol, isocyanate, quaternary ammonium salt monomer, trifluoromethylphenylboronic acid methyliminodiacetate, methacryloyloxyethyl ester, pentaerythrityl acrylate, 1,3-propenyl-sultone, 1,3-propenyl-sultone and acrylamide.
[0020] Preferably, the polymer solid electrolyte monomer includes at least one of vinylene carbonate, methyl methacrylate and acrylamide.
[0021] In some embodiments of the present invention, the inorganic material includes at least one of an inorganic solid electrolyte and an inorganic ceramic.
[0022] In some embodiments of the present invention, the active lithium salt includes at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium bis(oxalatoborate), lithium difluorooxalatoborate and lithium difluorophosphate.
[0023] In some embodiments of the present invention, the inorganic solid electrolyte includes at least one of an oxide solid electrolyte, a sulfide solid electrolyte, a halide solid electrolyte, a nitride solid electrolyte, a boride solid electrolyte, and a hydride solid electrolyte.
[0024] In some embodiments of the present invention, the inorganic ceramic includes at least one of metal oxides, nitrides, carbides, and borides.
[0025] In some embodiments of the present invention, in step (3), the drying includes forced air drying, vacuum drying or hot press drying.
[0026] In some embodiments of the present invention, the substrate includes a positive electrode sheet, a negative electrode sheet or a base film.
[0027] In a second aspect of the present invention, a biomass solid electrolyte film is provided. According to an embodiment of the present invention, the biomass solid electrolyte film is prepared by the above method.
[0028] In a third aspect of the present invention, the present invention provides a diaphragm-free solid-state battery. According to an embodiment of the present invention, the diaphragm-free solid-state battery comprises the above-mentioned biomass solid electrolyte film.
[0029] In a fourth aspect of the present invention, the present invention provides a solid-state battery. According to an embodiment of the present invention, the solid-state battery comprises the above-mentioned biomass solid electrolyte film.
[0030] In a fifth aspect of the present invention, the present invention provides a mechanical device. According to an embodiment of the present invention, the mechanical device includes the above-mentioned membrane-free solid-state battery or the above-mentioned solid-state battery.
[0031] The present invention has at least the following technical effects: (1) The present invention uses biomass sugar to prepare solid electrolytes. Biomass sugar materials are widely available and can be obtained from nature. They are environmentally friendly, water-soluble, renewable and low-cost. At the same time, biomass sugar has rich polar functional groups, which can improve the electrochemical performance of solid-state batteries and the compatibility of the positive and negative electrode interfaces, thereby improving the ionic conductivity of solid-state batteries.
[0032] (2) The present invention modifies biomass sugar by lithiation, grafts lithium ions onto the carboxyl or hydroxyl groups of biomass sugar, forms a single ion conductor, and improves the lithium ion conductivity of the system; the lithiated biomass sugar can make up for the active lithium ions consumed in the formation of CEI membrane and SEI membrane, and improves the interface stability of the positive and negative electrodes and the first coulomb efficiency; by regulating the degree of lithiation, the content of the remaining carboxylic acid and hydroxyl groups is controlled, and the carboxylic acid and hydroxyl groups can form a cross-linked structure through hydrogen bonds. Since the content of unstable groups at this time is much lower than that of the biomass sugar in the unlithiated state, the hydrogen bond cross-linked structure formed not only improves the mechanical properties of the solid electrolyte membrane and the ability to resist lithium dendrites, but also improves the battery cycle life.
[0033] (3) Lithiated biosaccharide can improve the compatibility between inorganic materials and polymer solid electrolyte monomers, thereby organically connecting the inorganic materials and polymer solid electrolyte monomers. It can not only wet the surface of the inorganic materials, but also help to evenly disperse the inorganic materials.
[0034] (4) Lithiated biomass sugar is a linear polymer. Through cross-linking polymerization with monomers, the chain mobility of the polymer is effectively increased, greatly enhancing the lithium ion transmission. In addition, by combining the characteristics of rigid biomass sugar and flexible polymer monomers, a rigid-flexible approach is adopted to improve the continuity and flatness of the interface contact between the positive and negative electrodes, and reduce the structural degradation caused by the volume change of the electrode. DETAILED DESCRIPTION
[0035] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.
[0036] In a first aspect of the present invention, the present invention provides a method for preparing a biomass solid electrolyte film. According to an embodiment of the present invention, the method comprises: S100: Mixing biomass sugar, alkaline lithium salt and first solvent
[0037] In this step, biomass sugar, alkaline lithium salt and the first solvent are mixed to obtain lithiated biomass sugar, wherein the biomass sugar includes at least one of chitosan, alginate and cellulose. By lithiating and modifying biomass sugar, lithium ions can be grafted onto the carboxyl or hydroxyl groups of biomass sugar to form a single ion conductor, which is beneficial to improve the lithium ion conductivity of the system. During the charge and discharge process, the electrolyte membrane will inevitably form a CEI film and a SEI film at the interface, thereby consuming part of the active lithium ions, and the lithiated biomass sugar can make up for this part of the lost lithium ions, reduce the reduction in ion conductivity caused by the loss of active lithium ions, and improve the stability of the positive and negative electrode interfaces and the first coulomb efficiency. The carboxyl and hydroxyl groups rich in the original biomass sugar can be reduced in the lithiated modified biomass sugar. The stability of these groups in the positive and negative electrodes is not as good as that of PVDF polymers, and they will decompose under high pressure and corrode lithium metal under low pressure. Therefore, the content of remaining carboxylic acid and hydroxyl groups can be controlled by regulating the degree of lithiation of biomass sugar. Carboxylic acid and hydroxyl groups can form cross-linked structures through hydrogen bonds. Since the content of unstable groups at this time is much lower than that of biomass sugar in the unlithiated state, the hydrogen bond cross-linked structure formed not only improves the mechanical properties of the solid electrolyte membrane and its ability to resist lithium dendrites, but also improves the battery cycle life.
[0038] According to an embodiment of the present invention, the first solvent includes at least one of N,N-dimethylacetamide, N-methylmorpholine-N-oxide, water, hydrochloric acid, formic acid, acetic acid and lactic acid.
[0039] According to an embodiment of the present invention, the alkaline lithium salt includes at least one of lithium hydroxide, lithium carbonate and lithium hydride. By selecting the alkaline lithium salt, the biomass sugar can be effectively modified, so that the lithium ions are successfully grafted onto the carboxyl or hydroxyl groups of the biomass sugar to form a single ion conductor, thereby improving the lithium ion conductivity of the system.
[0040] According to an embodiment of the present invention, the mass ratio of the alkaline lithium salt to the mass ratio of the biomass sugar is (1-35):100. For example, the mass ratio is 1:100, 5:100, 10:100, 15:100, 20:100, 25:100, 30:100, 35:100, etc. The inventors found that by controlling the mass ratio of the alkaline lithium salt to the mass ratio of the biomass sugar within the above range, the content of carboxylic acid and hydroxyl groups in the biomass sugar can be reduced, the content of unstable groups can be reduced, and the battery cycle stability can be improved; at the same time, the residual carboxylic acid and hydroxyl group content in the biomass sugar is avoided to be low, which reduces the mechanical properties of the electrolyte membrane.
[0041] According to an embodiment of the present invention, the solid content of the system after the biomass sugar, the alkaline lithium salt and the first solvent are mixed is 10% to 25%. The inventors have found that controlling the solid content of the system after the biomass sugar, the alkaline lithium salt and the first solvent are mixed within the above range is conducive to the full dissolution of the biomass sugar and the lithium reaction.
[0042] According to an embodiment of the present invention, the mixing temperature is 20° C. to 60° C. Controlling the mixing temperature within the above range helps the biomass sugar to be quickly and fully dissolved in the first solvent.
[0043] S200: mixing lithiated biomass sugar, polymer solid electrolyte monomer, inorganic material, active lithium salt, initiator and second solvent for polymerization
[0044] In this step, the lithiated biomass sugar, polymer solid electrolyte monomer, inorganic material, active lithium salt, initiator and second solvent are mixed and polymerized to obtain a precursor solution. The inventors found that the lithiated biomass sugar can improve the compatibility of inorganic materials and polymer solid electrolyte monomers. The lithiated biomass sugar can form covalent bonds or hydrogen bonds with hydroxyl groups or oxides on the surface of inorganic materials, and the other end forms hydrogen bonds or generates covalent bonds with polymer solid electrolyte monomers, thereby organically connecting the inorganic material and the polymer solid electrolyte monomer, which can not only wet the surface of the inorganic material, but also help to evenly disperse the inorganic material. The lithiated biomass sugar is a linear polymer. Through cross-linking polymerization with polymer solid electrolyte monomers and inorganic materials, the proportion of the crystalline region of the polymer can be greatly reduced, the mutual entanglement between chains can be reduced, the mobility of different polymer segments is increased, and the sites for complexation and dissociation with lithium ions are increased, thereby greatly enhancing the lithium ion transmission capacity. By combining the properties of rigid biomass sugar and flexible polymer monomers, a rigid-flexible approach is adopted to improve the continuity and flatness of the interface contact between the solid electrolyte and the positive and negative electrodes, and reduce the structural degradation caused by electrode volume changes.
[0045] It should be noted that the active lithium salt, the second solvent and the initiator are conventional materials in the art, and those skilled in the art can select them according to actual conditions. For example, the active lithium salt includes but is not limited to at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium bistrifluoromethane yellow imide, lithium bisfluorosulfonyl imide, lithium bisoxalate borate, lithium difluorooxalate borate and lithium difluorophosphate. The second solvent includes but is not limited to at least one of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, propylene carbonate, N-methylpyrrolidone, acetonitrile, dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, N,N-dimethylpropionamide, ethyl acetate, butyl butyrate, chloroform, dichloromethane, ether, toluene, acetone and tetrahydrofuran. The initiator includes, but is not limited to, at least one of azobisisobutyronitrile (AIBN), azobisisoheptanenitrile (ABVN), azobisisovaleronitrile (AMBN), dimethyl azobisisobutyrate (AIBME), azoisobutylcyanamide (CABN), diisopropyl azodicarboxylate (DIAD), azobiscyclohexylcarbonitrile (ACCN), benzoyl peroxide (BPO), di(2-ethylhexyl) peroxydicarbonate (EHP), tert-butyl perbenzoate (TBPB), methyl ethyl ketone peroxide (MEKP), mercaptobenzene, thiolates, and alkyl mercaptans.
[0046] According to an embodiment of the present invention, the mass ratio of lithiated biomass sugar, polymer solid electrolyte monomer, inorganic material, and active lithium salt is (15-25): (5-10): (50-90): (10-20). The inventors found that by controlling the mass ratio of lithiated biomass sugar, polymer solid electrolyte monomer, inorganic material, and active lithium salt within the above range, the rigid segments in the biomass sugar and the flexible segments in the polymer complement each other and jointly regulate the mechanical strength and flexibility of the solid electrolyte membrane, achieving a rigid and flexible effect; and the high ceramic content helps to improve the electrochemical stability of the electrolyte membrane and the thermal stability at high temperatures.
[0047] According to an embodiment of the present invention, the polymerization includes photopolymerization or thermal polymerization.
[0048] According to an embodiment of the present invention, the light source used for photopolymerization includes ultraviolet light or visible light, and the time of the photopolymerization is 1 min to 60 min.
[0049] According to an embodiment of the present invention, the heating temperature of the thermal polymerization is 30° C. to 120° C., and the heating time is 1 h to 80 h.
[0050] According to an embodiment of the present invention, the polymer solid electrolyte monomer includes vinylidene fluoride, tetrafluoroethylene, ethylene oxide, vinylidene fluoride-hexafluoropropylene, hexafluoropropylene, 1,3,5-trioxane, 1,3-dioxane, 1,4-dioxane, 1,3-dioxolane, 1,4-dioxane, dithiolane, boroxane, vinylene carbonate, vinyl vinyl sulfite, vinylene trithiocarbonate, vinyl acetate, methyl vinyl sulfone, ethyl vinyl sulfone, phthalic acid diacrylate, pentaerythritol tetraacrylate, methacrylate, ethylene di ... At least one of alcohol methacrylate, ethylene glycol dimethacrylate, ethylene glycol diacrylate, ethylene glycol acrylate, methyl methacrylate, propylene carbonate, acrylonitrile, lactam, lipoic acid, cyclosulfide, alkyl disulfide, tetrakis(hydroxymethyl)phosphonium chloride, melamine, olefinated monophosphine ligand, bisphosphine ligand, arginine methyl ester, arginine ethyl ester, acrylamide, methoxypolyethylene glycol, isocyanate, quaternary ammonium salt monomer, trifluoromethylphenylboronic acid methyliminodiacetate, methacryloyloxyethyl ester, pentaerythrityl alcohol acrylate, 1,3-propenyl-sultone, 1,3-propenyl-sultone and acrylamide.
[0051] Preferably, the polymer solid electrolyte monomer includes at least one of vinylene carbonate, methyl methacrylate and acrylamide.
[0052] According to an embodiment of the present invention, the inorganic material includes at least one of an inorganic solid electrolyte and an inorganic ceramic.
[0053] According to an embodiment of the present invention, the inorganic solid electrolyte includes at least one of an oxide solid electrolyte, a sulfide solid electrolyte, a halide solid electrolyte, a nitride solid electrolyte, a boride solid electrolyte, and a hydride solid electrolyte.
[0054] As an example, the oxide solid electrolyte includes, but is not limited to, one or more combinations of lithium lanthanum zirconium oxide (LLZO), niobium-doped lithium lanthanum zirconium oxide (LLZNO), tantalum-doped lithium lanthanum zirconium oxide (LLZTO), niobium-tantalum dual-doped lithium lanthanum zirconium oxide (LLZNTO), lithium lanthanum titanium oxide (LLTO), lithium aluminum titanium phosphate (LATP), yttrium titanium phosphate (LYTP), lithium aluminum germanium phosphate (LAGP), and lithium aluminum oxide (LiAlO2).
[0055] As an example, the sulfide solid electrolyte includes, but is not limited to, one or more combinations of lithium germanium phosphosulfide (LGPS), lithium phosphosulfur chloride (LPSCl), lithium thiophosphate (LPS), and glassy sulfides (Li2S-P2S5, Li2S-SiS2, Li2S-B2S3).
[0056] As an example, halide solid electrolytes include but are not limited to Li3OCl, LiI, Li5ZnI4, Li3OCl1-x Br x (where 0 < x < 1), Li2XCl4 (X includes Cd and / or Mg), Li2X′I4 (X′ includes Cd and / or Zn), LiMCl5X′′ (M includes one or more of La, Ta, Nb; X′′ includes any one of O, Cl, F, OH), Li 3-x Zr x M′ 1-x Cl6 (M′ includes one or more of Y, Er, Yb, Ho, Lu, 0 ≤ x ≤ 1) or a combination of one or more thereof.
[0057] As an example, the nitride solid electrolyte includes, but is not limited to, one or more combinations of LiPON, Li3N, Li7PN4, LiSi2N3.
[0058] As an example, the boride solid electrolyte includes, but is not limited to, one or more combinations of Li2B4O7, Li2O - B2O3 - P2O5, Li 6+2x [B 10 S 18 S x or a combination of one or more thereof.
[0059] As an example, the hydride solid electrolyte includes, but is not limited to, one or more combinations of Li3AlH6, LiBH4, LiNH2, Li2NH, LiBH4 - LiNH2, LiBH4 - LiX (X = Cl, Br, I).
[0060] According to an embodiment of the present invention, the inorganic ceramic includes at least one of metal oxides, nitrides, carbides, and borides.
[0061] As an example, the metal oxide includes at least one of, but is not limited to, alumina, titanium dioxide, zirconium dioxide, and magnesium oxide.
[0062] As an example, the nitride includes at least one of, but is not limited to, silicon nitride, titanium nitride, aluminum nitride, boron nitride, magnesium nitride, and zirconium nitride.
[0063] As an example, the carbide includes at least one of silicon carbide and boron carbide.
[0064] As an example, the boride includes at least one of, but is not limited to, silicon boride, vanadium boride, magnesium boride, and titanium boride.
[0065] S300: Apply the precursor solution on the substrate and dry
[0066] In this step, the precursor solution obtained in S200 is applied to the substrate and dried to obtain a biomass solid electrolyte film. It should be noted that the application method is a conventional method in the art, such as coating or spraying.
[0067] According to an embodiment of the present invention, drying includes air blowing drying, vacuum drying or hot press drying.
[0068] According to an embodiment of the present invention, the substrate includes a positive electrode sheet, a negative electrode sheet or a base film. For example, the precursor solution can be applied to the positive electrode sheet or the negative electrode sheet and dried to form a sheet-solid electrolyte film assembly. Alternatively, the precursor solution is applied to at least one side of the base film and dried to form a biomass solid electrolyte film on at least one side of the base film.
[0069] The base film is a conventional material in the art, for example, the base film includes polyethylene terephthalate (PET), ethylene terephthalate, polybutylene terephthalate, polyethylene (PE), polypropylene (PP), poly-1-butene, polyisobutylene, polybutadiene, polystyrene, polyvinyl chloride, polyvinylidene fluoride, polyacrylonitrile, polyvinylidene fluoride-hexafluoropropylene, cellulose, polyvinyl alcohol, polymethyl methacrylate, polyurethane, polycarbonate, polysulfate, aluminum oxide film, polyimide nonwoven film, polyaryl sulfone nonwoven film, silicone oil release film, non-silicon release film, fluorine release film or glass fiber. Further, the thickness of the base film is 1 μm~50 μm, preferably 2 μm~20 μm.
[0070] Preferably, the substrate is a positive electrode sheet or a negative electrode sheet. Applying the precursor solution to the positive electrode sheet or the negative electrode sheet and drying it can increase the contact area between the solid electrolyte layer and the sheet, reduce the interface impedance between the solid electrolyte layer and the sheet, and the formed positive electrode sheet-solid electrolyte film assembly and negative electrode sheet-solid electrolyte film assembly have excellent ionic conductivity.
[0071] In the second aspect of the present invention, the present invention proposes a biomass solid electrolyte film. According to an embodiment of the present invention, the biomass solid electrolyte film is prepared by the above method. As a result, the solid-state battery prepared by the biomass solid electrolyte film has high ionic conductivity and long battery cycle life. The biomass solid electrolyte film has excellent mechanical strength and toughness and strong processability. It should be noted that the features and advantages described above for the method for preparing the biomass solid electrolyte film are also applicable to the biomass solid electrolyte film, and will not be repeated here.
[0072] According to an embodiment of the present invention, the thickness of the biomass solid electrolyte film is 5um~10um. When the thickness of the solid electrolyte film is too low, lithium dendrites are easy to puncture and cause battery short circuit. When the thickness of the solid electrolyte film is too high, the increase in ion transmission distance will affect the rate performance of the battery. Therefore, the thickness of the biomass solid electrolyte film of the present application is controlled within the above range, and the battery has higher safety and rate performance.
[0073] In the third aspect of the present invention, the present invention proposes a diaphragm-free solid-state battery. According to an embodiment of the present invention, the diaphragm-free solid-state battery includes the above-mentioned biomass solid electrolyte film. As a result, the diaphragm-free solid-state battery has high ionic conductivity, long cycle life and reliable safety. It should be noted that the above-mentioned features and advantages described for the biomass solid electrolyte film are also applicable to the diaphragm-free solid-state battery, which will not be repeated here.
[0074] In a fourth aspect of the present invention, the present invention proposes a solid-state battery. According to an embodiment of the present invention, the solid-state battery comprises the above-mentioned biomass solid electrolyte film. As a result, the solid-state battery has high ionic conductivity, long cycle life and reliable safety. It should be noted that the features and advantages described above for the biomass solid electrolyte film are also applicable to the solid-state battery and will not be repeated here.
[0075] According to an embodiment of the present invention, a solid-state battery comprises a positive electrode sheet, a solid electrolyte film and a negative electrode sheet. For example, the positive electrode sheet, the solid electrolyte film and the negative electrode sheet are sequentially stacked and hot-pressed to prepare an integrated solid-state battery.
[0076] As an example, the main material of the positive electrode plate includes but is not limited to one or more combinations of nickel-cobalt-manganese ternary materials, nickel-cobalt-aluminum ternary materials, lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, and lithium vanadium phosphate; the main material of the negative electrode plate includes but is not limited to one or more combinations of graphite, graphene, carbon nanotubes, silicon-based alloys, silicon-oxygen negative electrodes, silicon-carbon negative electrodes, lithium metal, lithium alloy negative electrodes, lithium titanium oxides, transition metal oxides, and transition metal sulfides.
[0077] In a fifth aspect of the present invention, the present invention proposes a mechanical device. According to an embodiment of the present invention, the mechanical device includes the above-mentioned diaphragm-free solid-state battery or the above-mentioned solid-state battery. As a result, the mechanical device has a longer cruising range, higher safety performance and longer cycle life. It should be noted that the features and advantages described above for the solid-state battery are also applicable to the mechanical device and will not be repeated here.
[0078] The present invention is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.
[0079] Example 1
[0080] (1) Chitosan, lithium hydroxide and an aqueous solution are mixed at 45° C. to obtain lithiated chitosan, wherein the mass ratio of alkaline lithium salt to biomass sugar is 20:100, and the solid content of the system after mixing is 15%; (2) The lithiated chitosan, vinylene carbonate, LLZTO, LiTFSI, AIBN and DMF are mixed and polymerized at 60° C. for 12 hours to obtain a precursor solution; wherein the mass ratio of the lithiated biomass sugar, the polymer solid electrolyte monomer, the inorganic material and the active lithium salt is 15:5:70:10, the amount of the initiator added is 1wt% of the polymer solid electrolyte monomer, and the solid content of the precursor solution is 50%; (3) The precursor solution was applied onto PET and dried under 60° C. for 12 h to obtain a biomass solid electrolyte film.
[0081] Example 2
[0082] Different from Example 1, the biomass sugar in this example is alginate.
[0083] Example 3
[0084] Different from Example 1, the biomass sugar in this example is cellulose.
[0085] Example 4
[0086] Different from Example 1, the mass ratio of alkaline lithium salt to biomass sugar in this example is 10:100.
[0087] Example 5
[0088] Different from Example 1, the mass ratio of alkaline lithium salt to biomass sugar in this example is 30:100.
[0089] Example 6
[0090] Different from Example 1, the mass ratio of alkaline lithium salt to biomass sugar in this example is 40:100.
[0091] Example 7
[0092] Different from Example 1, the mass ratio of lithiated biomass sugar, polymer solid electrolyte monomer, inorganic material and active lithium salt in this example is 20:7:58:15.
[0093] Example 8
[0094] Different from Example 1, the mass ratio of lithiated biomass sugar, polymer solid electrolyte monomer, inorganic material and active lithium salt in this example is 25:10:50:15.
[0095] Example 9
[0096] Different from Example 1, the mass ratio of lithiated biomass sugar, polymer solid electrolyte monomer, inorganic material and active lithium salt in this example is 30:15:45:30.
[0097] Example 10
[0098] Different from Example 1, the polymer solid electrolyte monomer in this example is methyl methacrylate.
[0099] Embodiment 11
[0100] Different from Example 1, the polymer solid electrolyte monomer in this example is acrylamide.
[0101] Example 12
[0102] Different from Example 1, the inorganic material in this example is boride Li2B4O7.
[0103] Embodiment 13
[0104] Different from Example 1, the inorganic material in this example is boron nitride.
[0105] Embodiment 14
[0106] Different from Example 1, the active lithium salt in this example is LiDFOB.
[0107] Embodiment 15
[0108] Different from Example 1, the active lithium salt in this example is lithium difluorophosphate
[0109] Example 16
[0110] Different from Example 1, the initiator in this example is BPO.
[0111] Comparative Example 1
[0112] Different from Example 1, the biomass sugar in this example is not lithified.
[0113] Comparative Example 2
[0114] Different from Example 1, no polymer solid electrolyte monomer is added in this example.
[0115] Comparative Example 3
[0116] Different from Example 1, in this example, polymer solid electrolyte monomer is not added, but polymer solid electrolyte polyvinylene carbonate is added instead.
[0117] The following describes the battery performance test process and test results: (1) Ionic conductivity test method: A stainless steel-solid electrolyte-stainless steel symmetric battery was assembled and the battery was subjected to electrochemical impedance spectroscopy with a frequency range of 0.1 Hz-4 MHz and a test amplitude of 5 mV.
[0118] Assembly of solid-state batteries: 1) Positive electrode: The mass ratio of lithium nickel cobalt manganese oxide, PVDF and conductive carbon black is 96:2:2.
[0119] 2) Using lithium metal negative electrode as negative electrode.
[0120] 3) Stack the positive electrode sheet, solid electrolyte and negative electrode sheet in sequence and assemble them into a solid-state battery
[0121] 4) The battery was tested using the Xinwei battery performance test system with a voltage range of 2.7V-4.3V and charge and discharge conditions of 1 cycle at room temperature. The corresponding capacity retention rate was calculated after 100 cycles.
[0122] (2) Tensile strength test method: The solid electrolyte was cut into strips of 8 cm × 2 cm and the tensile strength was tested using a tensile testing machine at a tensile rate of 20 mm / min.
[0123] (3) Thermal shrinkage test: The solid electrolyte membrane was cut into 10 cm × 10 cm square strips and placed in a 150°C oven for 1 hour. The solid electrolyte membrane was taken out and the difference between the current length and width and the original length and width was measured. The difference divided by the original length and width was the shrinkage rate. The results of the tests of the batteries of Examples 1-16 and Comparative Examples 1-3 according to the above process and method are shown in Table 1: Table 1
[0124] From the data in Table 1, it can be seen that the appropriate lithiation of biomass sugars in Examples 1, 4-5 helps to improve the ionic conductivity while reducing the residual carboxyl and hydroxyl groups; over-lithiation in Example 6 will lead to a decrease in the number of carboxyl and hydroxyl groups that can complex with lithium ions, thereby reducing the ionic conductivity; the reduction in the number of residual carboxyl and hydroxyl groups will also lead to a decrease in the number of hydrogen bonds formed and a weakening of the cross-linking effect with the polymer solid electrolyte monomer, thereby reducing the corresponding tensile strength, elongation and thermal stability of the electrolyte membrane.
[0125] It can be seen from Example 1 and Examples 7-9 that reducing the content of inorganic materials with high ionic conductivity and high electrochemical window will lead to a decrease in the ionic conductivity of the electrolyte membrane and a decrease in the cycle stability of the matching high-voltage positive electrode; at the same time, due to the extremely high thermal stability of inorganic materials, the thermal shrinkage rate of components with high inorganic material content is lower.
[0126] It can be seen from Example 1 and Comparative Example 1 that lithiation of biomass sugar helps to improve the ionic conductivity of the electrolyte membrane, and reducing the number of carboxyl and hydroxyl groups in the biomass sugar helps to improve the cycle stability of the electrolyte membrane in the high-voltage positive electrode; and the reduction in the number of carboxyl and hydroxyl groups helps to improve the flexibility of the electrolyte membrane.
[0127] It can be seen from Example 1 and Comparative Examples 2-3 that cross-linking polymerization of biomass sugar and polymer solid electrolyte monomers can effectively increase the segment mobility of the polymer and reduce the crystallization area of the polymer, thereby enhancing lithium ion transmission.
[0128] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a biomass solid electrolyte film, characterized in that: include: (1) mixing biomass sugar, alkaline lithium salt and a first solvent to obtain lithiated biomass sugar, wherein the biomass sugar comprises at least one of chitosan, alginic acid and cellulose; (2) mixing the lithiated biomass sugar, polymer solid electrolyte monomer, inorganic material, active lithium salt, initiator and second solvent and polymerizing them to obtain a precursor solution; (3) Applying the precursor solution on a substrate and drying it to obtain a biomass solid electrolyte film.
2. The method according to claim 1, characterized in that: In step (1), the mass ratio of the alkaline lithium salt to the biomass sugar is (1-35):100; And / or, the solid content of the system after the biomass sugar, the alkaline lithium salt and the first solvent are mixed is 10% to 25%.
3. The method according to claim 1 or 2, characterized in that: In step (1), the mixing temperature is 20°C to 60°C; And / or, the alkaline lithium salt includes at least one of lithium hydroxide, lithium carbonate and lithium hydride.
4. The method according to claim 1 or 2, characterized in that: In step (2), the mass ratio of the lithiated biomass sugar, the polymer solid electrolyte monomer, the inorganic material, and the active lithium salt is (15-25): (5-10): (50-90): (10-20); and / or, the polymerization comprises photopolymerization or thermal polymerization; And / or, the light source used for the photopolymerization includes ultraviolet light or visible light, and the photopolymerization time is 1 min to 60 min; And / or, the heating temperature of the thermal polymerization is 30°C to 120°C, and the heating time is 1h to 80h; And / or, the polymer solid electrolyte monomer includes vinylidene fluoride, tetrafluoroethylene, ethylene oxide, vinylidene fluoride-hexafluoropropylene, hexafluoropropylene, 1,3,5-trioxane, 1,3-dioxane, 1,4-dioxane, 1,3-dioxolane, 1,4-dioxane, dithiolane, boroxane, vinylene carbonate, vinyl vinyl sulfite, vinylene trithiocarbonate, vinyl acetate, methyl vinyl sulfone, ethyl vinyl sulfone, phthalic acid diacrylate, pentaerythritol tetraacrylate, methacrylate, ethylene glycol methacrylate, At least one of vinyl acrylate, ethylene glycol dimethacrylate, ethylene glycol diacrylate, ethylene glycol acrylate, methyl methacrylate, propylene carbonate, acrylonitrile, lactam, lipoic acid, cyclosulfide, alkyl disulfide, tetrakishydroxymethylphosphonium chloride, melamine, olefinated monophosphine ligand, bisphosphine ligand, arginine methyl ester, arginine ethyl ester, acrylamide, methoxy polyethylene glycol, isocyanate, quaternary ammonium salt monomer, trifluoromethylphenylboronic acid methyliminodiacetate, methacryloyloxyethyl, pentaerythritol acrylate, 1,3-propylene-sultone, 1,3-propylene-sultone and acrylamide, preferably at least one of vinylene carbonate, methyl methacrylate and acrylamide; And / or, the inorganic material includes at least one of an inorganic solid electrolyte and an inorganic ceramic; And / or, the active lithium salt includes at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium bis(oxalatoborate), lithium difluorooxalatoborate and lithium difluorophosphate.
5. The method according to claim 4, characterized in that: The inorganic solid electrolyte includes at least one of an oxide solid electrolyte, a sulfide solid electrolyte, a halide solid electrolyte, a nitride solid electrolyte, a boride solid electrolyte and a hydride solid electrolyte; And / or, the inorganic ceramic includes at least one of metal oxides, nitrides, carbides and borides.
6. The method according to claim 1 or 2, characterized in that: In step (3), the drying includes air drying, vacuum drying or hot pressing drying; And / or, the substrate includes a positive electrode sheet, a negative electrode sheet or a base film.
7. A biomass solid electrolyte film, characterized in that: Prepared by the method according to any one of claims 1 to 6.
8. A diaphragm-free solid-state battery, characterized in that: Comprising the biomass solid electrolyte film as described in claim 7.
9. A solid-state battery, characterized in that: Comprising the biomass solid electrolyte film as described in claim 7.
10. A mechanical device, characterized in that: Including the membrane-free solid-state battery as described in claim 8 or the solid-state battery as described in claim 9.
Citation Information
Patent Citations
Chitosan derivative doped polymer solid electrolyte membrane as well as preparation method and application thereof
CN110707356A
Preparation method of composite solid electrolyte with soft filler
CN116826159A
Single-ion compound solid electrolyte, preparation and application thereof, and lithium ion battery
CN117691178A
Solid electrolyte and method for manufacturing the same
KR1020170108750A
Cited By
Preparation method of graphene modified mushroom mycelium lithium battery diaphragm
CN121123559A
Solid-state electrolyte membrane for wide-temperature-range lithium metal battery, battery and preparation method of solid-state electrolyte membrane
CN121439888A
Solid electrolyte membrane for lithium metal battery with wide temperature range, battery and preparation method thereof
CN121439888B